2015
DOI: 10.1111/ppa.12337
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium species and chemotypes associated with fusarium head blight and fusarium root rot on wheat in Sardinia

Abstract: Environmental conditions in Sardinia (Tyrrhenian Islands) are conducive to fusarium root rot (FRR) and fusarium head blight (FHB). A monitoring survey on wheat was carried out from 2001 to 2013, investigating relations among these diseases and their causal agents. FHB was more frequently encountered in the most recent years while FRR was constantly present throughout the monitored period. By assessing the population composition of the causal agents as well as their genetic chemotypes and EF-1a polymorphisms, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 35 publications
1
25
1
Order By: Relevance
“…Previous studies have shown the presence of Fusarium spp. in the wheat grains fungal community globally [9,25,59,61,62,[67][68][69][70] as well as in several Italian regions, including those investigated in this research [7,8,31,33,71] as well as in others [8,18,19,32]. In detail, Infantino et al [32] and Shah et al [18] showed that Fusarium incidence decreased from Northern to Southern Italian areas.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Previous studies have shown the presence of Fusarium spp. in the wheat grains fungal community globally [9,25,59,61,62,[67][68][69][70] as well as in several Italian regions, including those investigated in this research [7,8,31,33,71] as well as in others [8,18,19,32]. In detail, Infantino et al [32] and Shah et al [18] showed that Fusarium incidence decreased from Northern to Southern Italian areas.…”
Section: Discussionmentioning
confidence: 62%
“…Concentration of extracted DNA was estimated as previously described and the concentration of each DNA sample was adjusted to 20 ng/µL for qPCR analysis. Specific primers (Table S5) [87,88] were used for the quantification of six Fusarium species that might have potentially infected durum wheat kernels in the three investigated areas according to previous surveys conducted in the three regions on soft wheat, durum wheat and malting barley [7,31,33,70,71,73]. Tef1α primers were used for the quantification of durum wheat DNA (Table S5) [88].…”
Section: Quantification Of Fungal Biomass By Quantitative Real-time Pmentioning
confidence: 99%
“…At the same time, this entirely accessible dataset is essential for allowing further targeted studies in order to fully differentiate all included strains at both species and subpopulation levels, assuming that F. graminearum as well as F. culmorum are constituted by different subpopulations (Liang et al, 2014 ; Balmas et al, 2015 ; van der Lee et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while approximately two-thirds of the 27 F. culmorum strains from Italy possessed the 3ADON genotype, a chi-square test (df = 1) indicated 3ADON and NIV strains were segregating in nearly equal frequencies. Several studies have reported significant differences in trichothecene genotype frequencies, and these include the predominance of 3ADON in England and Wales (Jennings et al, 2004), Turkey (Yörük and Albayrak, 2012), Sardinia (Balmas et al, 2015), Tunisia (Kammoun et al, 2010), and several European countries (Tóth et al, 2004;Quarta et al, 2005). By contrast, surveys of FHB of wheat conducted in the Netherlands during 2000 and 2001 found NIV-producing F. culmorum predominated (Waalwijk et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Smith) Saccardo is the primary etiological agent of FCR in several countries in the Mediterranean and adjacent regions. This species was reported as the main FCR pathogen in Tunisia (Kammoun et al, 2009;Rebib et al, 2014), Sardinia (Balmas et al, 2015), Iran (Pouzeshimiab et al, 2014), and preliminary surveys suggest that it might be an important FCR pathogen in Algeria (Yekkour et al, 2015;Touati-Hattab et al, 2016). Nested within the B clade of trichothecene toxinproducing fusaria (Sarver et al, 2011), F. culmorum strains are segregating for two of the three known B type trichothecene chemotypes: deoxynivalenol (DON) + 3-acetyldeoxynivalenol (3ADON chemotype) and nivalenol (NIV chemotype) (Scherm et al, 2013).…”
Section: Introductionmentioning
confidence: 99%